2009
DOI: 10.3114/sim.2009.63.01
|View full text |Cite
|
Sign up to set email alerts
|

European species of Hypocrea Part I. The green-spored species

Abstract: At present 75 species of Hypocrea have been identified in temperate Europe. Nineteen green-spored species and their Trichoderma asexual states are here described in detail. Extensive searches for Hypocrea teleomorphs in 14 European countries, with emphasis on Central Europe, yielded more than 620 specimens within five years. The morphology of fresh and dry stromata was studied. In addition, available types of species described from Europe were examined. Cultures were prepared from ascospores and used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
283
4
15

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(314 citation statements)
references
References 74 publications
12
283
4
15
Order By: Relevance
“…Studies on Hypocrea demonstrated the overlapping morphological characteristics among species in the anamorph genus Trichoderma (e.g. Chaverri and Samuels, 2003;Jaklitsch, 2009), definitively showing that morphological distinctions were not reliable indicators of the degree of genetic divergence between species, and that morphological observations alone were insufficient for accurate identification of species of Trichoderma. To compensate for the lack of reliable morphological characters, research in Trichoderma biodiversity over the past 20 years has concentrated on the development of a variety of molecular markers to differentiate species, including isozymes, RAPDs, RFLP, AFLP and, most recently, the nucleotide sequences of various gene loci.…”
Section: Trichoderma Taxonomy a Tool To Assess Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on Hypocrea demonstrated the overlapping morphological characteristics among species in the anamorph genus Trichoderma (e.g. Chaverri and Samuels, 2003;Jaklitsch, 2009), definitively showing that morphological distinctions were not reliable indicators of the degree of genetic divergence between species, and that morphological observations alone were insufficient for accurate identification of species of Trichoderma. To compensate for the lack of reliable morphological characters, research in Trichoderma biodiversity over the past 20 years has concentrated on the development of a variety of molecular markers to differentiate species, including isozymes, RAPDs, RFLP, AFLP and, most recently, the nucleotide sequences of various gene loci.…”
Section: Trichoderma Taxonomy a Tool To Assess Diversitymentioning
confidence: 99%
“…In addition they discovered five unidentifiable isolate groups and 26 singular unidentified strains. The most comprehensive survey over any one biogeographic region was performed by Jaklitsch (2009Jaklitsch ( , 2011. He employed three genetic markers to identify 620 specimens of Hypocrea occurring in 14 countries in temperate regions of Europe, identifying 75 species including 29 previously undiscovered, thus greatly expanding the number of species known in that region.…”
Section: Trichoderma: Distribution and Biogeographymentioning
confidence: 99%
“…Species of the fungal genus Trichoderma (teleomorph in Hypocrea) are frequently encountered fungi, especially in soil and decaying wood (Klein and Eveleigh 1998;Kubicek et al 2008;Jaklitsch 2009;Druzhinina et al 2011;Friedl and Druzhinina 2012). Some of these species are known for their antagonistic activities towards plant pathogens, e.g., Botritis cinerea, Fusarium spp., Pythium spp., Rhizoctonia solani, Verticillium dahilae , and Sclerotinia spp.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Bissett (1984Bissett ( , 1991a established a new system of Trichoderma classification based on the branching pattern of conidiophores and the characteristics of phialides and conidia. After the introduction of molecular methods in Trichoderma taxonomy, the species concept of Trichoderma has changed dramatically (Chaverri and Samuels, 2003;Jaklitsch, 2009). In addition, the phylogenetic data helped to establish the relationship between anamorph Trichoderma and their related teleomorph Hypocrea (Chaverri and Samuels, 2003;Samuels et al, 1998Samuels et al, , 2002.…”
mentioning
confidence: 99%